PENANAMAN BUDI PEKERTI MELALUI PERTUNJUKAN WAYANG GOLEK GARAP PADAT - Jaka Rianta; Titin Masturoh (Gelar : Jurnal Seni Budaya, 2013)
The implanting of character or morals can be achieved through art appreciation and activity, forexample through the puppet show performance. Within performance art of puppet show, manyelements of moral education can be provided. This discussion promotes the problems about â€œhowthe character /moral elements in the puppet show performance can be used as the implanting ofmoral education for elementary students?â€. The goal of this research is to identify the moral elementsin the puppet show performance that can be seen though Sabet and vocabulary of utterance alongwith music accompaniment. This research also tries to describe the moral elements in the puppetshow performance as the moral teaching for elementary students. Based on the discussion, thereis a result that moral elements in wayang golek performance in shortened production can be seenon lakon element is chosen by suitable with the age from child to adult, sabet element by avoidingthe pornographic and sadism movement, utterance/ catur element by avoiding the harsh and dirtytalk and choose the respectful words. And music accompaniment /iringan elements by choosingthe respectful lyric and good songs.